PENGARUH KEPEMILIKAN ASING DAN DEWAN WANITA TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Mita Ulita Manurung; Makhdalena Makhdalena; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the effect of foreign ownership and women's boards on the financial performance of manufacturing companies listed on the IDX in 2017-2022. This research will be conducted on food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2017-2021 that have complete data (foreign ownership, women's boards and financial performance)There are 7 companies with a year of 35. This type of research is descriptive and quantitative research using Path Analysis. The results showed that foreign ownership and women's boards simultaneously and partially had no effect on the financial performance of food and beverage sub-sector manufacturing companies listed on the IDX in 2017-2021.Key Words: Foreign Ownership, Women's Board, Corporate Financial Performance